Genetic Diversity of Oil Palm (Elaeis guineensis Jacq.) of MTG Commercial Variety Based on Three RAPD Marker - Frynando Purba Girsang; Lollie Agustina P. Putri; Rosmayati Rosmayati (Universitas Sumatera Utara, 2019)
MTG variety is “moderate resistant” oil palm variety to ganoderma disease, these variety is not totally resistant to ganoderma disease, it means can be attacked and has the same morphological with other variety, so need to analyzed with moleculer marker to see genetic differences. The aim of this study is to know the pattern of DNA bands of oil palm based on RAPD marker OPA-13, OPD-13, OPH-13. This study was conducted in Plant Tissue Culture Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, Medan, from March 2017 to February 2018. Analyzed genetic materials were 26 DNA stocks of oil palm of commercial MTG variety from PT. Socfindo and resulted 100% of polymorphic percentage. The size of the DNA that produced a varied range between 424 to 2572 bp. Only 19 DNA samples that could be processed in software from the 26 DNA samples that analyzed, because there some samples that were not able to be amplified, so they did not meet the standardized precentage. Genetic distance measurement and dendrogram formation were analyzed using DARwin 6.0 software. The results of the analysis showed that 19 individuals were divided into three clusters with a total molecular diversity 49.87%. Coefficient of dissimilarity distance was 0 to 0,6.Key words: genetic diversity, RAPD markers, oil palm of MTG variety